Principles of realization of the foreign policy of Ukraine: the context of European integration - Величко, Дмитро Сергійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with the question of the principles of the foreign policy of Ukraine. The legal sources inwhich such principles were consolidated after independence of Ukraine have been analyzed. The currentlegislation of Ukraine in the sphere of foreign policy has also been analyzed. The principles of foreign policyin the context of the negotiations on the Association Agreement between the EU and Ukraine are revealed.